Vida em um laboratório de pesquisa e monitoramento ambiental - Rodrigues, Anny Caroliny de Lima (2015)
We aim here to go beyond the simple role of describing the daily routine of laboratory practices. We try to understand this tenuous line that connects science, nature and society. What is at stake is the study of the routine of a net of laboratories, connected to the National Institute of Science and Technology of Humid Areas (hereby INAU), which has the Humid Areas (hereby AUs) as its objective of research and a question about the policies of nature that go through the alliances between Psychology and Prevention of Disasters. Comprehending these nets is only possible if we consider the vicissitudes and contributions of AUs in the context of science, technology and innovation to the state of Mato Grosso. The interaction among environmental factors, human questions and laboratory creates a heterogeneous net of actants in which the relations among humans, environment and science is so imbricated that hardly we can think of one without considering the other, which justifies the growing number of researches, which has the Humid Areas as one of its strong source of scientific data. Observing the descriptions of each laboratory of INAU, we realized how different they are, but at the same time we can notice that both relate to a common objective, which is the contribution to the preservation of humid areas; such as the well being of the local community. Community that does not restrain only to the humans actants, but also expands to all the heterogeneous net, which composes the habitat of humid areas, human being or not human, including the plants, fungus, animals and also the water, one of the primary factors of what we denominated AUs in many laboratories. The popular knowledge is also considered inside the researches. When considering the popular and local knowledge inside the scientific knowledge, it transports the local population to inside the laboratory, allowing exchanges of knowledge that would not be possible if only the science was considered inside the research. When the psychology enters the laboratories, it does not produce only a narrative about the other, but a narrative that is also of the other. The psychologist may have the role of observer inside the laboratory, at the same time that he/she thinks in how the INAU deals with its data in relation to the sustainable management of the environment and environmental incidents, as well as how these may get to the population.